SC3 The use of checklists in simulated scenarios to support safe management of acute illness in primary care. (3rd November 2019) - Higham, Helen; Maloney, Anne; Eastwick-Field, Petronelle; Lawrence, Jo; Greig, Paul; Warren, Miss Rosie
Abstract : Background: Evidence suggests that GPs are managing more acutely unwell patients in their practices. 1 The RCGP curriculum for the care of acutely ill people includes: Recognising the signs of illness that require urgent intervention acting calmly in emergency situations and following agreed protocols working effectively in teams Simulation based education (SBE) and the use of checklists 2 in healthcare has been shown to improve outcomes in secondary care settings. It is reasonable to predict that teams in General Practice would benefit from similar training using realistic scenarios, supported by checklists created for primary care. Summary of project: Phase 1: We designed a training programme for GP settings using three simulated scenarios of recognised emergencies: acute coronary syndrome (ACS); paediatric anaphylaxis and newborn bronchiolitis. The training was delivered in ten practices initially and feedback was collected. Checklists to accompany the training were devised using a modified Delphi technique with an expert panel comprising GP multidisciplinary teams; consultants in emergency and respiratory medicine, anaesthetics and paediatric intensive care. The process was supported by observations made during the in-situ training and the template for checklists from the quick reference handbook (QRH) developed by the Association of Anaesthetists of Great Britain and Ireland (AAGBI - https://www.aagbi.org/safety/qrh/pdf-version-qrh ). Phase 2: Training in the use of the checklists has begun for the next group of 12 practices and a comparison between the training in phase 1 and phase 2 will be made using quantitative and qualitative methods. Summary of results: 172 multidisciplinary staff were trained in 20 practices from October 2018 to May 2019. The process of developing the checklists was complete after six iterations over three months for three topics:ACS; anaphylaxis and bronchiolitis. The checklist for anaphylaxis is shown in figure 1 . Course feedback: 100% of practices reported treating a medical emergency in the past year 60% of practices reported a wait >20 mins for an ambulance called to an acutely unwell patient 100% of participants thought checklists were helpful and comments from the training have informed additional modifications. Free text comments from participants uniformly placed high value on the simulation training Discussion: Our results so far support the use of SBE and checklists as a useful tool to support the delivery of safe care to acutely unwell patients in primary care settings. Further work is ongoing to complete a QRH for GP practices and to validate its use. References: https://www.kingsfund.org.uk/sites/default/files/field/field_document/managing-acuteillness- gp-inquiry-research-paper-mar11.pdf Arriaga AF, Bader AM, Wong JM, et al. Simulation-Based Trial of Surgical-Crisis Checklists. N Engl J Med . 2013;368(3):246–253. doi:10.1056/NEJMsa1204720.